SMART MANAGEMENT OF SPORTS FACILITIES IN THE DIGITAL AGE: A HOLISTIC MODEL FOR INTEGRATING INSTITUTIONAL PERFORMANCE AND ITS IMPACT ON SUSTAINABLE DEVELOPMENT - Hasan, Mayson Abdl Jalel Abdl (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. The challenges facing these facilities are increasing as a result of rapid technological developments, which requires the development of integrated models that incorporate modern technologies into their management. The results indicate that 70% of sports facilities suffer from poor integration among their internal departments, and 80% of them lack a comprehensive model for smart management. Objectives. The study aims to develop a holistic model for smart management by analyzing the current reality and identifying the necessary requirements, which enhances institutional sustainability. Method. The study employed a mixed-methods approach (descriptive-analytical, comparative, and applied), collecting data from a sample of 108 managers, technical and administrative staff in sports facilities. A developed questionnaire was used to assess the impact of smart management on performance integration and sustainability. Results. The results indicate a strong positive correlation (r = 0.71) between the application of smart management and achieving sustainable development, and PLS-SEM analysis revealed a total effect of 0.793 of smart management on sustainability through direct and indirect paths. Conclusion The importance of this study lies in providing a comprehensive strategic model that can contribute to improving institutional performance, increasing the effectiveness of internal processes, and enhancing innovation. Thus, this study represents an important scientific reference for officials and researchers in the field of sports management, opening new horizons for sustainable development in the sports sector.